2023
DOI: 10.3390/app13074408
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Parameter-Based Models for Walkability Evaluation

Abstract: Many scientific papers that deal with the topic of the pedestrian environment use a predefined form for assessing or evaluating its quality as a basic methodological instrument. The aim of this research is to emphasize the dimension of the available audit tools or methodologies in order to develop a full-scale database of indices that can be used for the measurement and evaluation of the pedestrian environment. By analyzing 115 research papers selected according to predefined selection criteria, the basic meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that the PEAT is a valid instrument with moderate to high inter-rater reliability for its major items (k-values between .46–.71, observed agreement ≥81%) and significant agreement between PEAT audits and GPS-derived measurements (0.77; k-values were ≥.57) ( Dragović et al, 2023 ; Joseph & Maddock, 2016 ; Troped et al, 2006 ; Zoellner et al, 2012 ). The PEAT and its’ manual can be accessed from Perelman School of Medicine, University of Pennsylvania’s website https://www.med.upenn.edu/beat/peat-materials.html…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that the PEAT is a valid instrument with moderate to high inter-rater reliability for its major items (k-values between .46–.71, observed agreement ≥81%) and significant agreement between PEAT audits and GPS-derived measurements (0.77; k-values were ≥.57) ( Dragović et al, 2023 ; Joseph & Maddock, 2016 ; Troped et al, 2006 ; Zoellner et al, 2012 ). The PEAT and its’ manual can be accessed from Perelman School of Medicine, University of Pennsylvania’s website https://www.med.upenn.edu/beat/peat-materials.html…”
Section: Methodsmentioning
confidence: 99%
“…Several spatial models have been widely used [28,36], combined or not with GIS [37] and multivariate analysis techniques [38][39][40][41][42][43][44]. Recently, urban studies have examined walkability using a wide range of variables of a diverse nature [45], e.g., geometric, functional, social [28], environmental [38], etc., which translate into pedestrian flow indicators [3], attractiveness [37], usability [28], comfort, safety, quality [39], etc. They have generally used graph theory and, above all, the space syntax method [3,[46][47][48] in particular.…”
Section: Theoretic Backgroundmentioning
confidence: 99%
“…This new approach of moving around by walking or cycling, along with public transport, is an excellent alternative that can improve urban mobility while also increasing a system's sustainability. A city's stakeholders can promote all of this by making changes in infrastructures, new rules to protect pedestrians and cyclists, and sustainable urban planning decisions [16][17][18][19].…”
Section: Urban Mobility and Walkabilitymentioning
confidence: 99%